Multi-response Optimization of Ultrasonic Assisted Enzymatic Extraction of Antioxidant Polysaccharides from Waste Ginkgo biloba Sarcotesta - Gui-Sheng Zhou (Faculty of Science, Chiang Mai University, 2020)
Chiang Mai Journal of Science